Węgrzy jako pars aliqua gentis Massagetum. Ślady późnoantycznej i wczesnośredniowiecznej uczoności w dziele Tomasza archidiakona Splitu. Część 2. Postrzeganie Massagetów. 1) Kontekst „scytyjski” - Spychała, Lesław (Instytut Historyczny Uniwersytetu Wrocławskiego, 2021)
This article is a continuation of the previously published Hungarians as pars aliqua gentis Massagetum. Sources of the late antic and early medieval era scholarship in the work of Thomas of Split (SAMAI 5, 2020, 155-195), which showed, based on Thomas of Split’s linking of the Massagetae ethnonym and the similarities between 9th century Hungarians and the Scythian peoples, the so called Scythian context, i.e. the identification in ancient and medieval writings (after ca. 1266) of the Massageteans with the land lying versus orientem.